Application of Knee Pain Exercise to Pain Intensity in Osteoarthritis Patients - Widiastuti, Agung; Utomo, Endrat Kartiko; Kartikasari, Annisa Yuli; Wulandari, Septiyana Indri (PT Inovasi Pratama Internasional, 2024)
Knee osteoarthritis in the elderly can cause pain due to joint capsules and cartilage damage in the bone joints. Osteoarthritis cases increase the risk of mobility disorders and have an effect on disability. Improving the quality of life in patients with joint disease is very necessary, namely by providing pain management through knee pain exercise. Knee pain exercise can maintain muscle strength so that it can reduce pain, increase functional activity in patients with knee osteoarthritis. This study aims to determine the effect of knee pain exercise in reducing pain intensity in osteoarthritis patients. The research design used Quasy Experiment One Group Pretest - Posttest Control Group Design. The population in this study were all knee osteoarthritis patients who experienced joint pain. The sampling technique used the purposive sampling method. Knee pain exercise was given 3 times a week and was carried out for 2 weeks, pain scale measurements using the Numeric Rating Scale (NRS) were carried out before and after knee pain exercise was given. The average pre-test results showed that the level of pain intensity in the intervention group was 5.05 and the average post-test value was 1.09, while in the control group the average pre-test results were 5.05 and the post-test value was still within the average range of 5.00. The Wilcoxon test results in the intervention group showed a p value of 0.0001 while in the control group a p value of 0.36 was obtained. The conclusion of this study is that there is a change in the level of pain before and after knee pain exercise in the intervention group, so there is an effect of knee pain exercise in reducing pain intensity in osteoarthritis sufferers.